Concordance of self-reported drug use and saliva drug tests in a sample of emergency department patients - Macdonald, S.; Cherpitel, C.; Stockwell, Tim; Martin, G.; Ishiguro, S.; Vallance, K.; Brubacher, J. (2014)
The purpose of this study was to assess the concordance of self-reports of cannabis, cocaine and amphetamines usage, with a saliva point-of-collection drug test, the DrugWipe 5+, in an emergency department (ED) setting. Methods: A random sample of people admitted to either of two emergency departments at hospitals in British Columbia, Canada were asked to participate in an interview on their substance use and provide a saliva test for the detection of drugs. Analyses: Concordance of self-reports and drug tests were calculated. Prior to DrugWipe 5+, sensitivity and specificity estimates were compared against a gold standard of mass spectrometry and chromatography (MS/GC). This was used as a basis to assess the truthfulness of self-reports for each drug. Results: Of the 1584 patients approached, 1190 agreed to participate, which is a response rate of 75.1%. For cannabis, among those who acknowledged use, only 21.1% had a positive test and 2.1% of those who reported no use had a positive test. For cocaine and amphetamines respectively, 50.0% and 57.1% tested positive among those reporting use, while 2.1% and 1.3%, respectively, reported no use and tested positive. Self-reports of cannabis and amphetamines use appear more truthful than self-reports of cocaine use.